1979
DOI: 10.1016/0022-1902(79)80206-7
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of uranium(IV) by N-phenylbenzohydroxamic acid and the structure of the reaction product: Chlorodioxo-N-phenylbenzohydroxamato-bis(Tetrahydrofuran)uranium(VI)[1]

Abstract: Uranium tetrachloride has been quantitatively oxidized via an oxygen transfer reaction with two equivalents of N-phenylbenzohydroxamic acid anion (PBHA) in tetrahydrofuran (THF) to form benzanilide and U0 2 C£(PBHA} (THF) 2. The structure of the uranyl complex has been determined by x-ray diffraction data collected by counter methods. The linear uranyl ion has an average u-o distance of 1.75(3) A, and is 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The associated antisymmetric absorption bands appear at 934, 897, and 906 cm -1 in the corresponding ATR-FTIR spectra. These data are in excellent agreement with values reported for [UO2(PBA)(THF)2Cl] (sym = 873 cm -1 and asym = 934 cm -1 ), 40 {[UO2(FHA)2]}n (sym = 827 cm -1 ), 31 [UO2(PBA)2DMSO] (asym = 910 cm -1 ), 35 [UO2(PBA)2DMF] (asym = 895 cm -1 ). 36 Uranyl chelation in the equatorial plane significantly lowers the oscillator strength and weakens the U=O bond order as the electron-donating ability of the ligands increases.…”
Section: Structuralsupporting
confidence: 90%
See 1 more Smart Citation
“…The associated antisymmetric absorption bands appear at 934, 897, and 906 cm -1 in the corresponding ATR-FTIR spectra. These data are in excellent agreement with values reported for [UO2(PBA)(THF)2Cl] (sym = 873 cm -1 and asym = 934 cm -1 ), 40 {[UO2(FHA)2]}n (sym = 827 cm -1 ), 31 [UO2(PBA)2DMSO] (asym = 910 cm -1 ), 35 [UO2(PBA)2DMF] (asym = 895 cm -1 ). 36 Uranyl chelation in the equatorial plane significantly lowers the oscillator strength and weakens the U=O bond order as the electron-donating ability of the ligands increases.…”
Section: Structuralsupporting
confidence: 90%
“…The orange-red color associated to both LMCT bands is a common feature among uranyl mono-and bishydroxamato complexes both in the solid state as well as in solution (vide infra). [34][35][36]40,[42][43][44][45][46] Ligand protonation equilibria Potentiometry. The protonation constants at 298.2(1) K of the conjugated bases NMAand PIPOhave been measured in triplicates by glass-electrode potentiometry in 0.1 M KNO3 solutions (black curve in Fig.…”
Section: Structuralmentioning
confidence: 99%
“…36 Notably, attempts to prepare [U-(pyNO) 4 ] from UCl 4 and excess K(pyNO) instead gave the uranyl complex [UO 2 (pyNO) 3 K] n (Figure 2) as an orange crystalline solid in 62% yield (Scheme 1). Oxidation of U IV , Mo V , V III by O atom abstraction from hydroxamic acids was previously documented; 37,38 therefore, [UO 2 (pyNO) 3 K] n likely arose from oxygen atom abstraction from pyNO − by the oxophilic uranium cation. Formation of uranyl (U VI O 2 2+ ) specie(s) likely accounts for the observed instability of Electrochemistry.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[28] Prior to this point in 1980, such complexes had not been structurally characterized, although quantitative analysis and solvent extraction studies of hydroxamic acids with actinides had been reported. [29] The colorless complexes, Th 4 , where R = C(CH 3 ) 3 or CH 2 C(CH 3 ) 3 , as shown in Figure 4, were both soluble in hydrocarbons, but displayed very different coordination geometries. [27] The stereochemistry constraints placed on the complex, 12, from the tert-butyl substituents force the ligand to form a geometry around the thorium(IV) center that is nearly cubic (S 4 ).…”
Section: 14mentioning
confidence: 99%